The Correlation Of Green Chemistry And Environmental Knowledge On Students’ Environmental Care Behavior - Yuli Santosa, Ni Ketut; Sulistyowati, Lilik; Sukmaning Aji, Sandra (Riviera Publishing, 2023)
Green chemistry and environmental knowledge shape individual awareness and action towards environmental sustainability. The integration of both can become the basis for attitudes and behaviors more concerned about the environment. Based on this background, the objectives of this research is to analyze the level of green chemistry and environmental knowledge of students’ SMA Kristen Harapan Denpasar and its correlation to environmental care behavior. The research was conducted using a random sampling technique with a sample size of 100 students. This research's independent variables are green chemistry (X1) and environmental knowledge (X2). In contrast, the dependent variable is environmental care behavior (Y). The research instrument is a test to measure the level of green chemistry and environmental knowledge and a questionnaire to measure students' environmental care behavior. Data analysis was done using descriptive statistics and Product Moment correlation analysis, followed by a t-test and F-test using Microsoft Excel. Based on the research results, it can be concluded: the level of green chemistry and environmental knowledge of students’ SMA Kristen Harapan Denpasar in a good category, and there is a correlation between green chemistry and environmental knowledge on students’ environmental care behavior.